PENINGKATAN PELAYANAN KESEHATAN PRIMER DALAM UPAYA PENGENDALIAN TBC - Cahyaningrum, Ika; Jefry Ka'arayeno, Arie; Suhartini Woli, Onceniati; Kurniawan, Dimas (Jurnal LENTERA, 2025)
TB cases in East Java in 2023 increased. In the Wagir Health Centre area in September 2023 there were 66 cases from July to September 2023, where 2% of TB patients were found to be non-compliant with taking medication, there was still low awareness of family members of patients to conduct sputum examination to the health centre independently. In addition, not all cadres understand how TB is transmitted, and nutrition for TB patients. To overcome this, a community service activity ‘Improving Primary Health Care as an Effort to Control TB in the Wagir Health Centre Working Area’ was carried out. The purpose of this activity is to increase the role of Puskesmas in TB control efforts. The method of community service is by implementing a programme of supervision of taking medication for TB patients, contact investigation and health education activities for cadres. Activities were carried out by a team from the Faculty of Health Sciences, Tribhuwana Tunggadewi University Malang, the nurse in charge of the Wagir Health Centre Area TB control programme, and cadres. Activities were carried out from February to March 2024 in the Wagir Health Centre Working Area, Malang Regency. The results of the implementation of the drug compliance monitoring programme for 10 TB patients, contact investigations for 45 people in contact with patients, and health education for 35 cadres. It is hoped that monitoring and evaluation of the programme from the Puskesmas is needed periodically, to optimise the TB control programme in the Wagir Health Centre Area.